A Comparison of Clinical Outcomes After XEN Gel Stent and EX-PRESS Glaucoma Drainage Device Implantation. Issue 6 (June 2021) - Stoner, Ari M.; Capitena Young, Cara E.; SooHoo, Jeffrey R.; Pantcheva, Mina B.; Patnaik, Jennifer L.; Kahook, Malik Y.; Seibold, Leonard K.
Abstract : Precis: Although the XEN stent offers a lower risk of hypotony and choroidal effusions with fewer clinic visits postoperatively, its surgical success rate was inferior to the EX-PRESS shunt. Purpose: To compare the clinical efficacy and safety outcomes of the XEN stent and EX-PRESS glaucoma drainage device in glaucomatous eyes. Materials and Methods: One hundred eyes from 88 patients underwent ab interno XEN stent or EX-PRESS shunt implantation (52 XEN and 48 EX-PRESS) for uncontrolled glaucoma at the University of Colorado Eye Center. The primary outcome was surgical success defined as intraocular pressure (IOP) ≥6 and ⩽18 mm Hg, without reoperation for uncontrolled glaucoma, loss of light perception, or use of glaucoma medications (complete success). Secondary outcomes were the same requirements allowing for medications (qualified success), mean IOP, medication use, adverse events, and number of postoperative clinic visits in the first 3 months. Results: Baseline characteristics including glaucoma type and severity were similar between groups, with the exception of XEN patients having fewer men (17% vs. 46%), older patients (median age, 78 vs. 68), and a higher percentage of white patients (89% vs. 69%). Adjusted hazard ratio of failure of XEN relative to EX-PRESS was 3.94 (95% confidence interval, 1.73-9.00, P =0.001) for complete success and 1.61 (95% confidence interval, 0.40-6.38, P =0.501) for qualified success. There were significantly fewer postoperative clinic visits during the first 3 months in the XEN group (5.3 vs. 9.1 visits, P <0.001). The incidence of serous choroidal effusions and hypotony was significantly less after XEN compared with EX-PRESS (1 vs. 9, P =0.02 and 15 vs. 25, P =0.023, respectively). Three XEN stents (5.8%) required removal. Conclusions: In this population, although the XEN stent offers a better safety profile and fewer postoperative clinic visits, complete surgical success was inferior to the EX-PRESS shunt. Abstract : Supplemental Digital Content is available in the text.